The Role of Circular Economy Dimensions in Strengthening Sustainable Supply Chain Management - Lestari, Lucia Dyah; Ermawati, Wita Juwita; Cahyadi, Eko Ruddy (Dinasti Publisher, 2025)
This study aims to uncover the effect of circular economy practices on sustainable supply chain management and to identify which dimensions of the circular economy most significantly contribute to improving supply chain performance. The research was conducted between February and April 2025 in the Cigondewah area of Bandung City, West Java, known as a center for small and medium-sized textile industries. A quantitative approach was employed, utilizing surveys and documentation analysis. Data were collected from 120 textile business actors through structured questionnaires and interviews, supported by secondary data from industry reports and government sustainability policies. The findings demonstrate that the implementation of circular economy practices has a positive and significant influence on the performance of sustainable supply chains. Through dimensional analysis, the study reveals that Rethink, Refurbish, and Reuse strongly enhance cost efficiency; Reuse, Reduce, and Recycle improve agility; and Rethink, Repurpose, Reuse, and Recycle effectively support environmental sustainability. Social sustainability is primarily driven by Recycle, while Remanufacture and Recover require strategic improvement. Reliability is strengthened by Recycle, Repurpose, Reuse, and Rethink, but Recover remains a key challenge. In the dimension of responsiveness, Recycle performs well, while Remanufacture and Recover need targeted attention. These insights provide practical implications for prioritizing specific circular economy dimensions to advance supply chain sustainability in the textile sector.